Interpellation and Affect: Activating Political Potentials Across Primate Species at Jakhoo Mandir, Shimla - Solomon, Daniel Allen (Humanimalia, 2016)
Journalistic and environmentalist discourses casting urban monkeys as outsiders to city landscapes in India appear in concert with efforts to produce a separation between the species through mass translocation of monkeys to beyond city limits. The monkeys are rhesus macaques, and despite popular notions that they are outsiders to human worlds, they exist and sometimes even flourish in the material-symbolic environments of South Asian cities, villages, farms and pastures. Contrary to the predominant discourse on urban monkeys, rhesus at “monkey temples” like Jakhoo Mandir in Shimla demonstrate that nonhuman primates can participate in the production of shared material-semiotic environments. Monkey temples are the products of an adaptive social hybridization at the confluence of coevolutionary interrelation, human religious-ethical sentiment, and the ongoing affective labors of monkeys. The assumption of human political and spatial pre-eminence and its correlative in management practice, mass translocation, are not necessary preconditions for a world in which both humans and monkeys can flourish.